Kritik Rasionalisme Mohammed Arkoun terhadap Budaya Intelektual Arab-Islam - Manshur, Fadlil Munawwar (TAJDID, 2023)
The aim of this essay is to provide a comprehensive analysis of Mohammed Arkoun's rationalist evaluation of the intellectual culture within the Arab-Islamic context. This study employs a functional approach that aims to reinterpret religious concepts within the context of culture and the daily interactions of individuals in society. The study's findings indicate that Arkoun's critique of Islamic rationalism, as approached through the lens of historicism, exhibits a significant impact from current Western philosophers. Arkoun incorporates various Western philosophies and notions in his analysis of the passages of the Koran. In his exploration of Islamic beliefs, Arkoun draws upon several theoretical frameworks like poststructuralism, corpus, episteme, discourse, deconstruction, myth, and logocentrism. Arkoun employs semiotic theory and extends its application to the interpretation of Quranic passages, surpassing the boundaries of semiotics as a discipline. Furthermore, Arkoun undertook a comprehensive examination of the interpretations of the Al-Quran's verses, aiming to prevent any potential confusion, rectify interpretive inaccuracies, and safeguard the Muslim community from divergent understandings. (iii) Arkoun thinks that the symbolic construction of the Koran has exerted a profound influence on the collective consciousness and cognitive processes of humanity, hence serving as a source of inspiration to rectify one's thinking and direct individuals towards morally upright deeds.